2018
DOI: 10.1161/circulationaha.118.035377
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytic Leukemia 1 Bridges Epigenetic Activation of NADPH Oxidase in Macrophages to Cardiac Ischemia-Reperfusion Injury

Abstract: -Excessive accumulation of reactive oxygen species (ROS), catalyzed by the NADPH oxidases (NOX), is involved in the pathogenesis of ischemia-reperfusion (I/R) injury. The underlying epigenetic mechanism remains elusive. -We evaluated the potential role of megakaryocytic leukemia 1, or MKL1, as a bridge linking epigenetic activation of NOX to ROS production and cardiac ischemia-reperfusion injury. -Following I/R injury, MKL1 deficient (KO) mice exhibited smaller myocardial infarction along with improved heart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 59 publications
1
78
1
Order By: Relevance
“…It was also observed that MKL1 overexpression activated the CTGF promoter by 3.2× and TGF‐β treatment activated the CTGF promoter by 1.7×; combined, MKL1 overexpression and TGF treatment synergistically activated the CTGF promoter by 4.8× (Figure b). On the contrary, a dominant negative (DN) form of MKL1, which lacks the trans‐activation domain (Yu et al, ), diminished the activation of the CTGF promoter by TGF‐β treatment by 37% (Figure c). It was noteworthy that when a conserved SMAD3 binding site within the CTGF promoter was mutated, MKL1 was unable to activate the CTGF promoter (Figure d), which indicated that MKL1 binding to the CTGF promoter might depend on SMAD3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that MKL1 overexpression activated the CTGF promoter by 3.2× and TGF‐β treatment activated the CTGF promoter by 1.7×; combined, MKL1 overexpression and TGF treatment synergistically activated the CTGF promoter by 4.8× (Figure b). On the contrary, a dominant negative (DN) form of MKL1, which lacks the trans‐activation domain (Yu et al, ), diminished the activation of the CTGF promoter by TGF‐β treatment by 37% (Figure c). It was noteworthy that when a conserved SMAD3 binding site within the CTGF promoter was mutated, MKL1 was unable to activate the CTGF promoter (Figure d), which indicated that MKL1 binding to the CTGF promoter might depend on SMAD3.…”
Section: Resultsmentioning
confidence: 99%
“…Megakaryocytic leukemia 1 (MKL1) is a transcriptional modulator known to bridge cytoskeletal reshuffling to stress response. MKL1 orchestrates a myriad of cellular responses to environmental and intrinsic stimuli including inflammation (Yu et al, ; Yu, Fang et al, ), oxidative stress (Yu et al, ), aging (Petrini et al, ), hypoxia (D. Chen et al, ; Yang et al, ), and mechanoresponse (Kuwahara et al, ). Mounting evidence portrays MKL1 as a key regulator of myofibroblast maturation and fibrogenesis (Small, ).…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assays were performed essentially as described previously . In brief, chromatin in control and treated cells was cross‐linked with 1% formaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assays were performed essentially as described previously. [34][35][36][37][38][39][40][41][42] In brief, chromatin in control and treated cells was cross-linked with 1% formaldehyde. Cells were incubated in lysis buffer (150 mM NaCl, 25 mM Tris-HCl pH 7Á5, 1% Triton-X-100, 0Á1% SDS, 0Á5% deoxycholate) supplemented with protease inhibitor tablet and phenylmethylsulphonyl fluoride.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…This issue of the journal contains a detailed examination of the role of MKL1 in the myocardial response to IR injury 11 . Mice lacking MKL1 were protected against IR injury, manifesting smaller infarcts and better cardiac function measured by echocardiography after 45 minutes of coronary artery occlusion followed by 24 hours reperfusion 11 .…”
Section: References: 15mentioning
confidence: 99%